Capital structure choices in technology firms: Empirical results from Polish listed companies - Marcin Kedzior; Barbara Grabinska; Konrad Grabinski; Dorota Kedzior (Journal of Risk and Financial Management, 2020)
The main aim of the paper is the identification of capital structure determinants, with a special emphasis on investments in the innovativeness of Polish New Technology-Based Firms (NTBFs). Poland is a unique country in that it is an emerging market that was also promoted in 2018 to the status of a developed country. The study sample consisted of 31 companies listed in the Warsaw Stock Exchange that are classified as high-tech firms and covers the period 2014-2018. The following factors influencing the capital structure were analyzed: internal and external innovativeness and the firm's size, liquidity, intangibility, age, profitability, and growth opportunities. The results of the research provide empirical evidence that liquidity, age, and investments in innovativeness determine capital structure, which provides an additional argument supporting the trade-off theory and the modified version of the pecking order theory. More specifically, the results suggest that companies whose process of investment in innovativeness is based on the external acquisition of technology are able to attract external financing, while the process based on internally generated innovativeness (R&D activity) deters external capital. The results are interesting for policymakers in emerging markets.
Keywords: 330; capital structure; intangibility; internal and external innovativeness; New Technology-Based Firms (NTBFs)